The Role of Social Media in Sustainability Oriented Practices An Exploratory Study - Ramzan, Fahad (2014)
Media, which was once seen as social institutions, came under criticism with the emergence of private media. It was argued that private media was more about profit than social purposes. But with the emergence of social media (like blogs, Facebook, twitter etc.) the important of media as social institution can be seen as increasing. In USA, France, Spain and other European countries there is a rapid growth in the use of social media and its influence is acknowledged in different arena’s including business and marketing. This study explores the role of social media as an institution towards making business responsible / sustainability oriented practices of business organisations. There has been quite a lot of practice literature regarding the role of social media and CSR or sustainability - it appears to focus on the aspects ranging from “communications” or “building relations” with stakeholders, engaging and influencing constituents towards responsible practices. Another dimension of sustainability or CSR that is being discussed is about transparency – that through discussion in various social media there is transparency to customers about the products or services, to others about how it treats employees and such. Such discussions in articles in press and also in reports by consultants leads us to ask the question what role does social media play have in for sustainability for firms operating in Malaysia – can social media become a social institution that can hold businesses responsible? Can they influence business organisations to integrate social or environmental issues into their strategies? If so how are global firms adopting or using social media in the context of sustainability oriented business strategies? And could there be a difference of the influence of social media in different sectors. This study outlines what different social media can play in different aspects of sustainability / responsible business practices in organisations operating in different sectors. Relevant literature related to social media and business and also social media and sustainability issues is gleaned to identify different themes to provide an initial framework or questions to make the inquiry. The method on enquiry for this study is qualitative and involves discourse / analysis. The sources for these discourses are primary as well as secondary – interviews of Malaysian CSR practitioners and business executives in general are conducted and also discussions in different internet forums or blogs are used as a source for discourses. This analysis focuses on identifying how different social media could have an influence on holding businesses to be responsible – different social media’s influence on different dimensions of sustainability oriented business practices. In addition an attempt is made to elicit and analyse data to propose an operational framework for organizations to have a positive impact on stakeholders related to their sustainable business practices using social media technologies.